2016
DOI: 10.1080/10242694.2016.1158439
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of the ministry of defence’s budget: methodological design and results for the Spanish economy

Abstract: This article analyses the economic impact of the expenditure budget of the Spanish Ministry of Defence (MoD) and its Autonomous Agencies (AA), distinguishing direct, indirect and induced effects. The input-output methodology is used to find intersectoral effects on the rest of the economy. The article quantifies the economic impact in terms of production, gross value added (GVA), employed population, tax revenue, and also in terms of its contribution to the gross domestic product (GDP) of Spain in 2010. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Daddi [27] investigate the impact of ME on GDP in Italy, the results showed that there is a military burden that has significant effects on GDP, promoting "peacekeeping" productivity and humanitarian missions that reduce insecurity from the external threat and implicitly of the investments and the jobs. García et al [28] analyze the influence of the allocation of the defense budget in Spain and its autonomous agencies and mention the effects of the cross-sectoral effects on the rest of the economy. The results show that the activity in the military sector and the activity of the agencies generated 1.2% of the GDP of the country and 1.7% of the total employment during 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Daddi [27] investigate the impact of ME on GDP in Italy, the results showed that there is a military burden that has significant effects on GDP, promoting "peacekeeping" productivity and humanitarian missions that reduce insecurity from the external threat and implicitly of the investments and the jobs. García et al [28] analyze the influence of the allocation of the defense budget in Spain and its autonomous agencies and mention the effects of the cross-sectoral effects on the rest of the economy. The results show that the activity in the military sector and the activity of the agencies generated 1.2% of the GDP of the country and 1.7% of the total employment during 2010.…”
Section: Literature Reviewmentioning
confidence: 99%